Division of states of Brazil in homogeneous groups used to statistics data the tourist industry and gross domestic product - Giannotti, Juliana Di Giorgio; Souza, Tania Mara Melquiades de (Revista Turismo em Análise, 2009)
The tourism embraces several sectors and actors of the economy and contributes on socio-economic development of regions where it installs. In order to characterize the 27 States of Brazil with respect to information the tourist industry and of the Gross Domestic Product, a cluster analysis was performed by Complete Linkage hierarchical clustering method, it was considered 16 variables. The result was: cluster 1 with 22 States and the lowest averages; cluster 2 with three States and the highest number of tourist carriers; cluster 3 with the State of Rio de Janeiro and the second best averages in; cluster 4 with the State of Sao Paulo and the highest averages. This analysis allowed the formation of States of Brazil clusters with a high homogeneity within-group and heterogeneity between-group. The cluster analysis with variables of tourism was recommended to distinguish tourist regions and guide actions in this sector.